The Himalayan Glaciation: Myth and Reality - Fort, Monique (Journal of Nepal Geological Society, 1995)
The frequency, age and type of glaciation in the Himalayas remain a matter of controversy and uncertainty. In this paper, current knowledge of Quaternary glaciation on both the south and north sides of the Central Nepal Himalayan range is reviewed in the light of recent data dealing with the palaeoclimatic evolution of the Himalaya-Tibet ensemble during the Late Cenozoic. Besides the global climatic factor, the Himalayan glaciation was mostly generated and controlled, in its regional extent, by topographical factors.